How hurricanes affect employment and wages in local labor markets - Ariel R. Belasen; Solomon W. Polachek (Institute for the Study of Labor (IZA), 2008)
This paper adopts a generalized-difference-in-difference (GDD) technique outlined in Ariel R. Belasen and Solomon W. Polachek (IZA Discussion Paper #2976) to examine the impact of hurricanes on the labor market. We find that earnings of the average worker in a Florida county rises over 4% within the first quarter of being hit by a major Category 4 or 5 hurricane relative to counties not hit, and rises about 1% for workers in Florida counties hit by less major Category 1-3 hurricanes. Concomitantly, employment falls between 1 and 5% depending on hurricane strength. On the other hand, the effects of hurricanes on neighboring counties have the opposite effects, moving earnings down between 3 and 4% in the quarter the hurricane struck. To better examine the specific shocks, we also observe sectoral employment shifts. Finally, we conduct a time-series analysis and find that over time, there is somewhat of a cobweb with earnings and employment rising and falling each quarter over a two-year time period.
urn:nbn:de:101:1-2008032097
Keywords: J23; 330; Exogenous shock; difference-in-difference estimation; local labor market; earnings; employment; sectoral shifts; Sturm; Regionaler Arbeitsmarkt; USA; Arbeitsmarkt; Beschäftigung; Lohn; Florida